Analisa Kelayakan Tarif Pdam Kota Dumai Berdasarkan Pengembalian Biaya penuh (Full Cost Recovery) Proyek - Dewi Herlina; Ari Sandhyavitri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Dumai, one of the largest city in Riau Province, has only served 6% of its total population’s needs of water supply, which mean there are only about 16.000 of 280.000 citizen in this city which have been served by PDAM with 80 L/s supplying ability and just 50% efficiency. Therefore, improvements of water supply should be top priority, which means it needs a relatively big amounts of investment based on the feasibility study. In this case, to obtain a proportional investment it needs to analyze the Full Cost Recovery of this project. The ultimate goal of this research is to analyze the Economic Feasibility for PDAM of Dumai city for 25 years later with a turnover provisions at the 20th year. The feasibility study in this research is based on economic analysis with two alternatives; water treatment with 80 L/s capacity up to projection age and raising to160 L/s capacity at the 5th year. This economic analysis uses five indicators; Net Present Value (NPV) of benefit and cost flow,Internal Rate of Return (IRR), Benefit Cost Ratio (BCR), Break Event Point (BEP) and sensitivity analysis, whereas the calculation in this study using the approximate estimation. The calculation in this research uses 12% of interest rate and 6% of inflation, and results Rp. 61.098.871.064,- of investments for an 80 L/s capacity water treatment with price Rp. 7.000,-/m3 for a household and Rp 9.000,-/m3 for an industrial consumption with Rp. 4.444.807.908 , - of NPV with 1,135 BCR and 16,829 % IRR. As for the capacity of 160 l / sec obtained an investment of Rp . 99,657,097,694 , - with a tariff of Rp . 5.700 , - for Household and Rp . 8.000 , - for an industrial consumption with Rp6.670.266.335 , - of NPV with 1,122 BCR and 16,433 % IRR with investment feasibility analysis above shows that all the parameters are well worth to be invested. Keywords : Investment Feasibility Analysis , Investment Feasibility indicators , NPV , BCR , IRR , BEP , Sensitivity Analysis .